Marketing Challenges / Cases and Exercises - Lovelock H. Christopher; Weinberg B. Charles (Mcgraw Hill Book Company, 1986)
The Nature of Marketing, Market Selection, Product Policy, Distribution and Delivery Systems, Marketing Communication, Pricing, Marketing Research, Strategic Market Planning, Organizing and Implementing the Marketing Effort, Appendixes.
The Nature of Marketing, Market Selection, Product Policy, Distribution and Delivery Systems, Marketing Communication, Pricing, Marketing Research, Strategic Market Planning, Organizing and Implementing the Marketing Effort, Appendixes.